Effect of midsole structures on cushioning properties of running shoes - Wee, Raynor Pen Yi (2019)
The study investigated the effect of midsole structures on heel cushioning properties of running shoes. Test specimens of different structures were made using EVA foam. Test specimens were subjected to a vertical impact test of 5.0 J with a spherical striker. For the first phase, three different structures, namely, column, hole and row were used for comparison. They were compared against each other and against a control which was an uncut piece of foam. For the second phase, three column structures with different cross-sectional areas, namely, low, medium and high, were compared against each other. For the third phase, a foot last was used as a striker and the experiment was scaled to the heel of a foot. Three different column structures with different number of columns were compared against each other. Using data from the impact trials, the linear loading rate, relative energy dissipated, and peak force were calculated. The linear loading rate was used as the indicator for cushioning performance. For Phase 1, the column structure was found to have the best cushioning properties amongst the three midsole structures. For Phase 2, the low cross-sectional area column structure was found to have the best cushioning properties amongst the three midsole structures with different cross-sectional areas. For Phase 3, the size of columns did not affect the linear loading rate of the three different midsole structures, when total cross-sectional area was kept constant. Findings suggest that a decrease in cross-sectional area leads to a decrease in linear loading rate, indicating that cushioning performance was improved.